2020
DOI: 10.1371/journal.pone.0232492
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral differences at scent stations between two exploited species of desert canids

Abstract: Coyotes (Canis latrans) and kit foxes (Vulpes macrotis) are desert canids that share ecological similarities, but have disparate histories with anthropogenic pressure that may influence their responses towards novel stimuli. We used remote cameras to investigate response to novel stimuli for these two species. We predicted that coyotes (heavily pressured species) would be more wary towards novel stimuli on unprotected land (canid harvest activities are permitted) than in protected areas (canid harvest activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Remote cameras have been deployed to target kit foxes in the Great Basin (i.e., western Utah and Oregon), Mojave (Utah, Nevada, and Arizona), and Chihuahuan (i.e., New Mexico and Mexico) deserts, and have provided data on kit fox distribution (Milburn and Hiller 2013), occupancy (Richards 2017), habitat selection (Hall et al 2013b), reproductive rates (Kluever et al 2013), interspecific interactions (Robinson et al 2014), and behavior (e.g., activity patterns, vigilance and investigative behaviors; Hall et al 2013a;Sergeyev et al 2020). To date, camera-based monitoring of kit foxes has relied on the application of lures or attractants (e.g., Hall et al 2013b;Richards 2017), natural aggregation points (e.g., water sources; Hall et al 2013a), or known den sites (Kluever et al 2013).…”
Section: Camera-based Surveysmentioning
confidence: 99%
See 1 more Smart Citation
“…Remote cameras have been deployed to target kit foxes in the Great Basin (i.e., western Utah and Oregon), Mojave (Utah, Nevada, and Arizona), and Chihuahuan (i.e., New Mexico and Mexico) deserts, and have provided data on kit fox distribution (Milburn and Hiller 2013), occupancy (Richards 2017), habitat selection (Hall et al 2013b), reproductive rates (Kluever et al 2013), interspecific interactions (Robinson et al 2014), and behavior (e.g., activity patterns, vigilance and investigative behaviors; Hall et al 2013a;Sergeyev et al 2020). To date, camera-based monitoring of kit foxes has relied on the application of lures or attractants (e.g., Hall et al 2013b;Richards 2017), natural aggregation points (e.g., water sources; Hall et al 2013a), or known den sites (Kluever et al 2013).…”
Section: Camera-based Surveysmentioning
confidence: 99%
“…For example, Kluever et al (2013) found cameras were more reliable than visual observations (e.g., via spotting scope; Cypher et al 2000) in determining accurate counts of adult and juvenile kit foxes at known dens. Similarly, cameras have proven to be an effective tool in investigating individual behavior of kit foxes, including vigilance (antipredator behavior) at water sources (Hall et al 2013a) and variation in investigative tendencies between sites with and without harvest (Sergeyev et al 2020). Although cameras have been effectively used to estimate kit fox occupancy (Richards 2017) and patterns of co-occurrence with coyotes (Robinson et al 2014), low detection rates may limit its applicability in some systems.…”
Section: Camera-based Surveysmentioning
confidence: 99%